Production and Characterization of Ackee Apple (Blighia sapida) Seeds and African Star Apple (Chrysophyllum albidum) Seeds Oil Mixtures and their Biodiesel - Olumoroti, Israel Adebayo; Oyelaran, Ajani Olatunde; Bolaji, Bukola (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
This paper focused on the characterization of oils and biodiesels derived from Ackee apple seeds and African star apple seeds obtained from local markets. The oils from individual seeds and their mixtures at varying ratios were characterised for relative density, free fatty acid, acid, iodine, and saponification, which yielded 0.91 g/cm3, 1.06 mg-KOH/g, 2.12 mg-KOH/g, 38.36mg-iodine/100g, and 195.74 mg-KOH/g of ackee seed oil, respectively. And 0.89 g/cm3, 2.105 mg-KOH/g, 4.2 mg-KOH/g, 52.49 mg-iodine/100 g, and 227.7 mg-KOH/g of African star apple seed oil, respectively. The highest relative density of 0.9064 g/cm3 and free fatty acid of 3.73 mg-KOH/g were achieved from the mixture of ackee apple and African star apple seeds’ oils at 80 and 20%, respectively, while the highest saponification of 221.264 mg-KOH/g and iodine of 49.66 mg-iodine/100 g were obtained from the oil mixture of 20 and 80%, respectively. Also, the oils extracted from the seeds, were subjected to a transesterification process to produce biodiesel. 144°C flash point, 206°C fire point, and 2.8°C cloud point were obtained from the biodiesel of the oil mixture of 20 and 80%, respectively. Further analysis of the mixtures showed low volatility and high resistance to fire due to their high flash and fire points. The highest value recorded for the flash point is lower when compared with some other seed oils flash points; however this value is higher than the standard flash point for biodiesels .Highest boiling point of 64°C was attained at an oil mixture ratio of 60 and 40%, respectively. This value is too low compared to the normal boiling point range of 315-350°C for biodiesels, and the high acid values recoded for the mixtures make the oils inedible. The oils, however, have advantages over other edible seed oils as they will serve as valuable ingredients in the soap-making industries since they are not competing with food resources